Et in aliena castra - Dorandi, Tiziano (Gruppo editoriale Tab Srl, 2024)
The writings of Tiziano Dorandi collected in this volume focus above all on Diogenes Laertius, but also on Plato, Aristotle, on cynicism and stoicism, on Epicurus and Philodemus of Gadara: they show with particular clarity how decisive the contribution of philology has been for the history of ancient thought.